Evaluation of the Problems Experienced by Students in Their Schools According to the Opinions of Special Education Teachers in the Context of Inclusive Education - Acar, Elif; Erol, Yusuf Celal (Fırat University, 2026)
The aim of this study is to determine whether special education students experience problems at school, if they do, to reveal the problems they experience, to determine the reasons for these problems and to offer comprehensive solutions to these problems. In line with this purpose, special education teachers were asked whether their students experience problems at school, if so, what these problems are, what causes these problems and how comprehensive solutions can be produced to these problems. In the study, a qualitative research method was adopted and a phenomenological design was used. As a sampling method, the criterion sampling method, one of the purposeful sampling methods, was preferred. The study group consists of 56 special education teachers working in the city center of Elazığ. 27 of the teachers are male and 29 are female. The data of the study were collected using a semi-structured interview form. The obtained data were analyzed using the content analysis method. In the study, the participants stated that special education students experience problems at school. It was stated that these problems were related to the school, class and lessons. It was stated that students had communication and social interaction problems, other students showed hitting, pushing and spitting behavior, they had adaptation and language development problems and their self-care skills were not sufficiently developed. It was emphasized that these problems were caused by the physical structures of schools and classes, their course content and developmental characteristics. Teachers suggested that educational support should be provided to families and legislation and curriculum should be improved.

Bu çalışmanın amacı, özel eğitim öğrencilerinin okullarında sorun yaşayıp yaşamadıklarının tespit edilmesi, eğer sorun yaşıyorlarsa, yaşadıkları sorunların ortaya konulması, bu sorunların sebeplerinin belirlenmesi ve bu sorunlara kapsayıcı çözüm önerileri getirilmesidir. Bu amaç doğrultusunda, özel eğitim öğretmenlerine, öğrencilerinin okulda sorun yaşayıp yaşamadıkları, yaşıyorlarsa bu sorunların ne olduğu, bu sorunların neyden kaynaklandığı ve bu sorunlara nasıl kapsayıcı çözümler üretilebileceği sorulmuştur. Çalışmada, nitel araştırma yöntemi benimsenmiş ve olgubilim deseni kullanılmıştır. Örneklem yöntemi olarak ise, amaçlı örnekleme yöntemlerinden ölçüt örnekleme yöntemi tercih edilmiştir. Araştırmanın çalışma grubunu Elazığ il merkezinde görev yapan 56 özel eğitim öğretmeni oluşturmaktadır. Öğretmenlerden 27’si erkek, 29’u kadındır. Araştırmanın verileri, yarı yapılandırılmış görüşme formu kullanılarak toplanmıştır. Elde edilen veriler, içerik analizi yöntemi ile analiz edilmiştir. Çalışmada, katılımcılar, özel eğitim öğrencilerinin okullarında problem yaşadıklarını ifade etmişlerdir. Bu problemlerin, okul, sınıf ve dersler ile ilgili olduğu dile getirilmiştir. Öğrencilerin, iletişim ve sosyal etkileşim problemleri yaşadıkları, diğer öğrenciler vurma, itme ve tükürme davranışı gösterdikleri, uyum ve dil gelişimi problemi yaşadıkları ve öz bakım becerilerinin yeterince gelişmediği ifade edilmiştir. Bu sorunların, okul ve sınıfların fiziki yapılarından ve derslerinden içeriklerinden ve gelişim özellikleri ve kaynaklandığı vurgulanmıştır. Öğretmenler, ailelere eğitici destek sağlanmasını ve mevzuat ve müfredatın iyileştirilmesini önermişlerdir.
Özel Eğitim Öğretmenlerinin Görüşlerine Göre Öğrencilerinin Okullarında Yaşadıkları Sorunların Kapsayıcı Eğitim Bağlamında Değerlendirilmesi
Keywords: Applied and Developmental Psychology (Other); Uygulamalı ve Gelişimsel Psikoloji (Diğer)